Shortened Length of Stay Improves Financial Outcomes in Living Donor Kidney Transplantation - Villa, Manuel; Siskind, Eric; Sameyah, Emil; Alex, Asha; Blum, Mark; Tyrell, Richard; Fana, Melissa; Mishler, Marni; Godwin, Andrew; Kuncewitch, Michael; Alexander, Mohini; Israel, Ezra; Bhaskaran, Madhu; Calderon, Kellie; Jhaveri, Kenar D.; Sachdeva, Mala; Bellucci, Alessandro; Mattana, Joseph; Fishbane, Steven; Coppa, Gene; Molmenti, Ernesto (International Journal of Angiology, 2013)
Kidney transplantation is the preferred clinical and most cost-effective option for end-stage renal disease. Significant advances have taken place in the care of the transplant patients with improvements in clinical outcomes. The optimization of the costs of transplantation has been a constant goal as well. We present herein the impact in financial outcomes of a shortened length of stay after kidney transplant.
Keywords: kidney transplantation; postoperative protocols; transplant outcomes; economic outcomes; arithmetic analysis